2020
DOI: 10.1111/clr.13559
|View full text |Cite
|
Sign up to set email alerts
|

Flapless immediate implant placement and provisionalization in periodontal patients: A retrospective consecutive case‐series study of single‐tooth sites with dehiscence‐type osseous defects

Abstract: Objective To assess the clinical outcomes of flapless, immediate implant placement with simultaneous augmentation of dehiscence defects and immediate provisional restoration. Materials and Methods Retrospective evaluation of 40 periodontal patients who received a flapless immediate implant for single‐tooth replacement with simultaneous augmentation of dehiscence defects and immediate provisional restoration, at follow‐up periods ranging from 1 year minimum to 7 years maximum. Dehiscence defects were augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 47 publications
(109 reference statements)
0
28
0
Order By: Relevance
“…Te attached gingiva closely surrounding the edge of the implant can efectively resist friction and pressure. Ticker gums mean sufcient blood supply, and can maintain an ideal biological width, which contributes to the early soft tissue sealing, healing and anti-infection of implants, and improves the initial stability [19,20]. Te follow-up of this study found that the success rate of implants in minimally invasive surgery group was not signifcantly diferent from that in conventional surgery group one year after the repair operation was completed.…”
Section: Discussionmentioning
confidence: 58%
“…Te attached gingiva closely surrounding the edge of the implant can efectively resist friction and pressure. Ticker gums mean sufcient blood supply, and can maintain an ideal biological width, which contributes to the early soft tissue sealing, healing and anti-infection of implants, and improves the initial stability [19,20]. Te follow-up of this study found that the success rate of implants in minimally invasive surgery group was not signifcantly diferent from that in conventional surgery group one year after the repair operation was completed.…”
Section: Discussionmentioning
confidence: 58%
“…Case selection mainly relates to buccal bone wall integrity. The body of evidence supporting type I placement in severely damaged sockets is considered weak (Tonetti et al, 2019), although clinical studies are emerging specifically evaluating IIP under these challenging conditions (Assaf et al, 2017; Sicilia‐Felechosa et al, 2020; Slagter, Meijer, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This difference could be attributed to the role of soft tissue grafting in compensating for the labial tissue loss after immediate implant placement 30,31 . Additionally, our result was more favorable than that reported by Sicilia‐Felechosa and colleagues, where flapless IIP with bone grafting and connective tissue grafting was used 32 . In that study, the implant success rate was 98%.…”
Section: Discussionmentioning
confidence: 47%
“…30,31 Additionally, our result was more favorable than that reported by Sicilia-Felechosa and colleagues, where flapless IIP with bone grafting and connective tissue grafting was used. 32 In that study, the implant success rate was 98%. Esthetic failure (PES ≤ 7) was observed in two out of 40 cases and eight patients (21.6%) exhibited a 1-2 mm soft tissue recession.…”
Section: Discussionmentioning
confidence: 83%